Sukuk Market Development and Macro-Economic Factors: Empirical Evidence from Pakistan - M. Razwan Sheikh; Faiz-ur-Rahim, (ASIAN Journal of International Peace & Security (AJIPS), 2024)
This study is an attempt to find out the association between macro-economic variable and Sukuk market development in Pakistan. Macro-economic variables are considered as the mainstay for the development of Sukuk markets. Therefore, the scope of this study is to find out the association between macro-economic variable viz. gross domestic product, inflation, exchange rate, trade openness and Sukuk market development in Pakistan. This research work is carried out by employing, explanatory research design and utilizing the secondary data to assess the relationship between Sukuk market development and macro-economic variables in Pakistan. Consequently, VECM technique was used to assess this relationship for the period of 15 years from 2008-2022. The findings of this study demonstrated that only two variables i.e. GDP and exchange rate have shown significant relationship with Sukuk market development in the short-run. However, in the long-run all variables i.e. GDP, exchange rate and trade openness, except inflation have shown significant relationship with Sukuk market development in Pakistan. The results of this work may instigate the policy makers to step-up with such innovative strategies, which can provide conducive growth for macro-economic variables, and, consequently, lead to flourish the development of Sukuk market in the country.